Office design and its impact on employee productivity at Logistik Department (PDRM) - Rahmawaty, Sirajuddin (2014)
The purpose of this research is to present the effect of work designs of work place have on the productivity of the Police Force. Quantitative date were collected via a questions distributed amongst the Police Officers in Logistic Department at Bukit Aman. A total of 145 officers completed the questionnaire. The result shows that furniture, noise, lighting, temperature and have a significant positive relationship with productivity while spatial arrangement has no significant relationship.